DAMPAK PERNIKAHAN DINI TERHADAP KETAHANAN KELUARGA: TINJAUAN MAQASHID SYARIAH - Muhamad Arif Iqbal (Kaffah: Jurnal Pendidikan dan Sosio Keagamaan, 2026)
This study aims to analyze the impact of early marriage on family resilience from the perspective of the maqasid sharia (Islamic principles), which encompasses the preservation of religion (hifz al-din), life (hifz al-nafs), intellect (hifz al-'aql), offspring (hifz al-nasl), and property (hifz al-mal). This study used a quantitative approach with a literature review method. Data were obtained from various sources, including books, scientific journal articles, research findings, and documents relevant to early marriage, family resilience, and the maqasid sharia. Data analysis was conducted through the identification, classification, and interpretation of various previous research findings related to the research topic. The results indicate that early marriage has a complex impact on family resilience. From an economic perspective, couples in early marriages tend to experience limited income and financial dependence, which impact family stability. From a psychological perspective, emotional immaturity has the potential to increase domestic conflict and reduce the quality of marital relations. From an educational perspective, low levels of education due to early marriage impact limited decision-making and child-rearing skills. From a maqasid sharia perspective, early marriage can hinder the optimal preservation of life, intellect, offspring, and wealth if not accompanied by adequate preparation. However, religious values, family support, and the couple's commitment to practicing Islamic teachings can be factors that strengthen family resilience. This study concludes that early marriage tends to negatively impact family resilience, although under certain conditions, the goal of a harmonious family can still be achieved if supported by adequate individual and environmental preparation.